2015
DOI: 10.1017/s1355617715000971
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Is Associated with Impaired Striatal Function during Inhibition with Normal Cortical Functioning on Functional MRI

Abstract: The aim of the present study was to investigate the effect of HIV infection on cortical and subcortical regions of the frontal-striatal system involved in the inhibition of voluntary movement. Functional MRI (fMRI) studies suggest that human immunodeficiency virus (HIV) infection is associated with frontostriatal dysfunction. While frontostriatal systems play a key role in behavioral inhibition, there are to our knowledge no fMRI studies investigating the potential impact of HIV on systems involved during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
(89 reference statements)
1
14
0
Order By: Relevance
“…Interestingly, executive function was also found to be positively affected by drug switching in our study, measured by an improvement on the Groton Maze Learning Test and moreover on the SST task, which has become a standard measure of response inhibition (Logan and Cowan 1984 ). Data on SST performance in PWH are scarce, though a recent study reported that drug-naïve PWH showed comparable SSRTs with respect to healthy controls but longer RTs (Du Plessis et al 2015 ). In the NNRTI study, we found that SSRTs were longer in participants on efavirenz before switching to rilpivirine, suggesting a detrimental effect caused by efavirenz with a loss of correct response inhibition, which might be restored by switching to rilpivirine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, executive function was also found to be positively affected by drug switching in our study, measured by an improvement on the Groton Maze Learning Test and moreover on the SST task, which has become a standard measure of response inhibition (Logan and Cowan 1984 ). Data on SST performance in PWH are scarce, though a recent study reported that drug-naïve PWH showed comparable SSRTs with respect to healthy controls but longer RTs (Du Plessis et al 2015 ). In the NNRTI study, we found that SSRTs were longer in participants on efavirenz before switching to rilpivirine, suggesting a detrimental effect caused by efavirenz with a loss of correct response inhibition, which might be restored by switching to rilpivirine.…”
Section: Discussionmentioning
confidence: 99%
“…However, the INSTI group findings, where no change was observed, would suggest that the NNRTI findings were the result of the switch form from efavirenz to rilpivirine rather than a repeated measures effect. Although De Plessis et al (Du Plessis et al 2015 ) showed comparable SSRTs between healthy controls and drug-naïve PWH, no study is currently available on SSRT differences between healthy controls and people PWH on efavirenz or rilpivirine containing cART. Secondly, the PROMs are self-reported questionnaires, so we cannot fully exclude a response shift bias, as is an intrinsic limitation of all self-reported questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that inhibitory control deficits occur in HIV+ individuals with co-occurring alcohol or stimulant use disorders (Rippeth et al, 2004; Schulte, Müller-Oehring, Sullivan, & Pfefferbaum, 2011); however, as with set-shifting, there is little evidence that HIV-infection alone contributes to measurable deficits in inhibition. Although the overall estimated effect of HIV-infection on measures of inhibition was small, there is evidence that HIV may functionally alter brain regions involved in inhibitory control processes (du Plessis et al, 2015). Specifically, on a measure of reactive response inhibition (i.e., withholding a response following a “stop” signal), HIV+ individuals were found to display a pattern of hypoactivation in the right and left putamen.…”
Section: Discussionmentioning
confidence: 99%
“…Persons living with HIV (PLWH) typically act more impulsively than seronegative individuals in a variety of PFC-mediated behavioral measures ( Chang et al, 2017 ; Fujiwara et al, 2015 ; Hardy et al, 2006 ). Nevertheless, even in the absence of behavioral deficits, PLWH display increased fMRI activity in the anterior cingulate cortex (ACC) region of the PFC and striatum when making risky choices ( Connolly et al, 2014 ; du Plessis et al, 2015 ). Furthermore, viral load is increased within the PFC, striatum, and thalamus ( Nath, 2015 ), while brain volume within these regions ( Janssen et al, 2015 ; Nichols et al, 2019 ; Sanford et al, 2018 ), and fronto-striatal resting state connectivity ( Ipser et al, 2015 ; Janssen et al, 2017 ; Ortega et al, 2015 ; Plessis et al, 2014 ), are decreased in PLWH.…”
Section: Introductionmentioning
confidence: 99%